Glial fibrillar acidic protein in the cerebrospinal fluid of Alzheimer's disease, dementia with Lewy bodies, and frontotemporal lobar degeneration. Issue 2 (11th November 2015) - Ishiki, Aiko; Kamada, Maki; Kawamura, Yuki; Terao, Chiaki; Shimoda, Fumiko; Tomita, Naoki; Arai, Hiroyuki; Furukawa, Katsutoshi
Abstract: Biomarkers in the cerebrospinal fluid (CSF) are currently regarded as indispensable indicators for accurate differential diagnosis of neurodegenerative disorders. Although high levels of astrocyte‐secreted glial fibrillar acidic protein (GFAP) in the CSF of patients with Alzheimer's disease (AD) have been reported, the levels of GFAP in the CSF have not been fully investigated in other neurological disorders that cause dementia, such as dementia with Lewy bodies (DLB) and frontotemporal lobar degeneration (FTLD). In this study, we determined the levels of GFAP in the CSF of healthy control subjects and AD, DLB, and FTLD patients to address two questions: (i) Do the levels of GFAP differ among these disorders? and (ii) Can GFAP be used as a biomarker for the differential diagnosis of these neurodegenerative disorders? The levels of GFAP in AD, DLB, and FTLD patients were significantly higher than those in the healthy control subjects. Although the levels of GFAP were not significantly different between AD and DLB patients, a higher level of GFAP was observed in FTLD patients than in AD and DLB patients. It is concluded that representative neurological disorders causing dementia were associated with higher levels of GFAP in the CSF. We propose the following mechanism concerning the amount of glial fibrillar acidic protein (GFAP) in the cerebrospinal fluid (CSF) in Alzheimer's disease (AD), dementia with Lewy bodies (DLB), and frontotemporal lobar degeneration (FTLD). The increase in the release of GFAP into CSF is considered to reflect the sum of degeneration of astrocytes and astrocytosis. The sum of degeneration and astrocytosis or the GFAP release could be in the order of FTLD > DLB > AD > normal condition. Abstract : We propose the following mechanism concerning the amount of glial fibrillar acidic protein (GFAP) in the cerebrospinal fluid (CSF) in Alzheimer's disease (AD), dementia with Lewy bodies (DLB), and frontotemporal lobar degeneration (FTLD). The increase in the release of GFAP into CSF is considered to reflect the sum of degeneration of astrocytes and astrocytosis. The sum of degeneration and astrocytosis or the GFAP release could be in the order of FTLD > DLB > AD > normal condition.